Determinants of Dividend in Indian Pharmaceutical Industry - A Study of Select Companies - Kamalaveni, D.; Kalaiselvi, S.; Sabitha, D. (Indian Journal of Finance, 2010)
Today, the Indian Pharmaceutical industry is in the front rank of India's science - based industries with wide ranging capabilities in the complex field of drug manufacturing and technology. As a highly organized sector, the Indian pharma industry is estimated to be worth $4.5 billion, growing at about 8 to 9 percent annually. It ranks very high in the third world, in terms of technology, quality and range of medicines manufactured.